Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Institut Agama Islam Tasikmalaya - Ajang Ramdani (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this study was to see the effectiveness of entrepreneurship courses on students' interest in entrepreneurship. The research method used is an experimental method with a quasi-experimental approach. The location of this research was conducted in two class groups at the Tasikmalaya Islamic Institute. 1 class is used as an experimental class for applying entrepreneurship courses and 1 class is used as a control class using conventional methods or existing methods. The results showed that there was an increase in students' interest in entrepreneurship after being given treatment in entrepreneurship courses. So it can be concluded that entrepreneurship courses are effective in increasing students' interest in entrepreneurship.